Handbook of industrial organization - Arrow, Kenneth J (Ed); Intriligator, Michael D (Ed) (Amsterdam Elsevier, 1998)
Handbook of Industrial Organisation is in two volumes. The first volume content are-Determinants of firm and market organisation, Analysis of market behaviour and volume two contents are-Empirical methods and results, International issues and comparisons
Keywords: INDUSTRIAL ORGANIZATION (ECONOMIC THEORY)-HANDBOOKS; MANUALS; ETC; ECONOMIC POLICY; ECONOMIC DEVELOPMENT